2015
DOI: 10.1115/1.4031389
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Modeling Techniques for Polydispersed Droplet Spectra in Steam Turbines

Abstract: Within steam turbine flows, condensation phenomena give rise to complex droplet spectra that can span more than two orders of magnitude in size. To predict the behavior of the two-phase flow and the resulting losses, the interactions between the vapor phase and droplets of all sizes must be accurately calculated. The estimation of thermodynamic losses and droplet deposition rates, in particular, depends on the size range and shape of the droplet spectrum. These calculations become computationally burdensome wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Particles (droplets) form by condensation from the vapor phase in both ambient and industrial settings and are crucial elements in many current health, 1-5 environmental, [6][7][8][9][10] and industrial [11][12][13][14] challenges. Fine refractory fumes, for example, form in metallurgical and combustion processes, H 2 SO 4 -H 2 O nanodroplets form in exhaust stacks and volcanic eruptions, and water can condense in low pressure turbomachinery, perturbing the flow and reducing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Particles (droplets) form by condensation from the vapor phase in both ambient and industrial settings and are crucial elements in many current health, 1-5 environmental, [6][7][8][9][10] and industrial [11][12][13][14] challenges. Fine refractory fumes, for example, form in metallurgical and combustion processes, H 2 SO 4 -H 2 O nanodroplets form in exhaust stacks and volcanic eruptions, and water can condense in low pressure turbomachinery, perturbing the flow and reducing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…More recently Afzalifar et al 22 did further investigations and especially Hughes et al 19 considered the influence of different expansion rates. In line with previous findings the differences between the discrete spectrum method and the monodispersed method are remarkable for high as well as for low expansion velocities.…”
Section: Droplet Size Distribution Modelingmentioning
confidence: 99%
“…The same area based droplet radius is applied to evaluate the droplet growth rates in the moment method. (Note that in White 21 and Hughes et al 19 detailed studies about the moment closure problem are provided.) The various mean radii are defined by…”
Section: Droplet Size Distribution Modelingmentioning
confidence: 99%
“…Hughes et al. 25 compared the moment methods with Lagrangian full spectrum methods and demonstrated that it achieves satisfactory accuracy (errors in Sauter mean radius and entropy gain due to phase change ≤ 10%) for primary nucleation at the expansion rates present in LP steam turbines. Further details regarding the modelling methods can be found in Hughes.…”
Section: Rans Solver For Non-equilibrium Steam Flowsmentioning
confidence: 99%